EFFECTS OF ANTICOAGULANT AND ANTIARRHYTHMIC THERAPY IN ATRIAL FIBRILLATION - XOJIYEV B.B (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Resume. Arterial fibrillation (AF) is the most common cardiac arrhythmia that requires treatment. The main points of treatment include relieving AF paroxysm and planned antiarrhythmic therapy. The article summarizes the main antiarrhythmic drugs used to relieve AF paroxysms and keep the sinus rhythm planned. Propafenone is unique in this series, available in two forms – oral and intravenous, which allows the drug to be used at all stages of relieving AF paroxysm and during planned antiarrhythmic therapy.